ANALISIS PUTUSAN PENGADILAN AGAMA MALANG TENTANG HAK TANGGUNGAN PADA SENGKETA EKONOMI SYARIAH (Studi Kasus Putusan Pengadilan Agama Malang nomor: 0689/Pdt.G/2017/PA.Mlg) - imawan, arip; Hadi, Abd (Universitas Muhammadiyah Surabaya, 2020)
The Malang Religious Court has the authority to decide cases on Islamic economic disputes. Decision numbered: 0689 / Pdt.G / 2017 / PA.Mlg is a ruling stating that they reject the plaintiff's claim regarding the cancellation of the mortgage. The formulation of the problem in this study was how the litigation procedure in the Sharia Economic Dispute Settlement of the Malang Religious Court and the legal basis for judges' consideration in deciding case number 0689 / Pdt.G / 2017 / PA.Mlg. This study used qualitative methods with primary data source for decision number 0689 / Pdt.G / 2017 / PA.Mlg and secondary data in the form of laws and regulations, DSN-MUI fatwa, documentation, and interview with judges of the Malang Religious Court. Conclusion Thesis, legal considerations used by the Panel of Judges in Decision Number: 0689 / Pdt.G / 2017 / PA.Mlg wereappropriate. These legal considerations used Law number 3 of 2006 and Law number 50 of 2009 concerning religious courts, Law number 4 of 1996 concerning mortgage rights and objects related to land, Law number 21 of 2008 concerning Islamic banking, DSN fatwa MUI number 11 / DSN-MUI / IV / 2000 concerning Kafalah and Perma number 2 of 2008 concerning Sharia Economic Law Compilation. However, in using consideration Permenkeu 106 / PMK.06 / 2013 was not appropriate because the Permenkeu had been revoked and was not valid because there was a Permenkeu 27 / PMK.06/2016.Â Key Words : Sharia Economic Disputes, Mortgage Rights,Â Religious Courts